Divisão sexual do trabalho e relações de gênero em contexto estuarino-costeiro amazônico - COSTA, Norma Cristina Vieira (Universidade Federal do Pará, 2019)
The article discusses the results of research conducted by the SocioEnvironmental Studies Coastal Group of the Federal University of Pará, Brazil – UFPA in various communities of traditional populations in the region of the Marine Extractive Reserve Caeté Taperaçu-Bragança-PA. It highlights how the sexual division of labor and access to paid work, in particular the treatment of crabs, works to update the socio-historical persistence of gender inequalities. Interesting enough, the reflection of this stability is based on the changes that have operated on the relations between men and women: the construction of strategic flexibilities in the sense of rebuilding of practices and values that, simultaneously, maintain the gender system. The inflexibility of the hierarchical and socially asymmetrical representations are anchored in the reproductive capacity of women.